The purpose of power : how to build movements for the 21st century - Garza, Alicia, 1981- (New York : One World, 2020)
"Coupled with the speed and networking capacities of social media, #blacklivesmatter was the hashtag heard round the world. But Alicia Garza well knew that the distance between a hashtag and real change would take more than a single facebook to cover. It would take a movement. Garza was a lifelong activist who had spent the previous decades educating herself on the hard lessons of organizing. She started as a kid, working on sexual education for her peers, and then moved on to major campaigns around housing, policing, and immigrant and labor rights in California and then nationally. The lessons she extracted were different from the "rules for radicals" that animated earlier generations of lefitists; they were also different than the charismatic, patriarchal model of the American Civil Rights Movement. She instead developed a mode of organizing based on creating deep connections with communities, forging multiracial, intersectional coalitions, and, most of all, calling in all sorts of people to join the fight for the world we all deserve. This is the story of an activist's education on the streets and in the homes of regular people around the country who found ways to come together to create change. And it's also a guide for anyone who wants to share in that education and help build sustainable movements for the 21st century at any level, whether you're fighting for housing justice in your community or advocating for a political candidate or marching in the streets or just voting. It's a new paradigm for change for a new generation of changemakers, from the mind and heart behind one of the most important movements of our time"--
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Social movements; Political participation